PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PADA BISNIS PERCETAKAN - Br. Ginting, Suriani; Pandia, Sonya Enda Natasha S.; Wailan’An, Evi Juita (Universitas Methodist Indonesia, 2023)
The printing business is growing along with the online printing business. The trend of online printing is increasing. The presence of online printing makes it easier for customers to print the documents they need without having to queue and wait. Nibun Printing is a printing services business that has been established since 2009 with the permanent customer of Nibun Printing being PDAM Tirtanadi Delitua Branch in terms of making fines and Tirtanadi logos at various events. The Partner's problem is that they don't understand the meaning of income and expenses, the Partner doesn't have a Financial Report. Nibun Printing does not prepare financial reports so it does not know the amount of income and costs for each period. Implementation of service activities is carried out by visiting partners to identify needs and provide training and assistance in preparing financial reports. Training activities are carried out by giving lectures and discussions first to explain the importance of financial reports in the printing business. Then it is continued with assistance and training in preparing financial reports. Through this activity Partners can understand the meaning of income and expenses in preparing Financial Reports. By providing training and assistance to Nibun Printing to be able to prepare financial reports in accordance with accounting standards, it can help partners to facilitate the preparation of financial reports in accordance with accounting standards. The prepared financial reports can be used to assist in obtaining external sources of funds so that this printing press continues to develop and able to expand his business.